Prognostic value of nectin-4 in human cancers: A meta-analysis - Liu, Rongqiang; Zhao, Kailiang; Wang, Kunpeng; Zhang, Lilong; Ma, Wangbin; Qiu, Zhengdong; Wang, Weixing (Frontiers in Oncology, 2023)
Background: Many reports have described that abnormal nectin-4 expression may be used as a prognostic marker in many tumors. However, these studies failed to reach a consensus. Here, we performed a meta-analysis to comprehensively evaluate the prognostic value of nectin-4 in cancers. Methods: Relevant studies were identified through a comprehensive search of PubMed, EMBASE and Web of science until August 31, 2022. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were used to evaluate the relationship between nectin-4 expression and overall survival (OS) and disease-free survival/progression-free survival/relapse-free survival (DFS/PFS/RFS). Odds ratios (ORs) with 95% CIs were applied to assess the relationship between nectin-4 expression and clinicopathologic features. Subgroup analysis was performed to explore the sources of heterogeneity. Sensitivity analysis and funnel plot were used to test the reliability of the results. All data analyses were performed using STATA version 12.0 software. Results: Fifteen articles involving 2245 patients were included in the meta-analysis. The pooled analysis showed that high nectin-4 expression was significantly associated with poor OS (HR: 1.75, 95% CI: 1.35–2.28). There was no relationship between high nectin-4 expression and DFS/PFS/RFS (HR: 178, 95% CI: 0.78–4.08).Subgroup analyses revealed that that high nectin-4 expression mainly presented adverse OS in esophageal cancer (EC) (HR: 1.78, 95% CI: 1.30–2.44) and gastric cancer (GC) (HR: 1.92, 95% CI: 1.43–2.58). We also found that high nectin-4 expression was associated with tumor diameter (big vs small) (OR: 1.96, 95% CI: 1.02–3.75), tumor stage (III-IV vs I-II) (OR: 2.04, 95% CI: 1.01–4.12) and invasion depth (T3+T4 vs T2+T1) (OR: 3.95, 95% CI: 2.06–7.57). Conclusions: Nectin-4 can be used as an effective prognostic indicator for specific cancers.